Preparation method of supported nitrogen-phosphorus-sulfur co-doped non-noble metal zinc-air battery catalyst

Through the preparation method of supporting nitrogen, phosphorus and sulfur co-doped non-precious metal zinc air battery catalyst, the non-precious metal single atoms are co-modified by nitrogen, phosphorus and phosphorus, the problems of high cost and low stability of zinc air battery catalysts are solved, and efficient oxygen reduction performance and stability are achieved.

CN120048926APending Publication Date: 2025-05-27NORTHWEST UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510206640.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-25
Publication Date
2025-05-27

AI Technical Summary

Technical Problem

The existing zinc air battery catalysts are costly and have low stability, making it difficult to effectively solve in large-scale industrial production and application.

Method used

A method for preparing a supported nitrogen, phosphorus and sulfur co-doped non-precious metal zinc air battery catalyst is adopted. The non-precious metal single atom is co-modified by nitrogen, phosphorus and phosphorus. Only one step of calcination is required to improve the oxygen reduction performance and stability of the catalyst.

Benefits of technology

It achieves efficient oxygen reduction performance and stability, reduces economic costs, solves the problems of high cost and low stability of zinc air battery catalysts, and has a great technological breakthrough.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120048926A_ABST
    Figure CN120048926A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a supported nitrogen-phosphorus-sulfur co-doped non-noble metal zinc-air battery catalyst, which comprises the following steps: firstly preparing a ZIF-8 carrier, then loading non-noble metal salt on the ZIF-8 carrier, and then preparing the supported nitrogen-phosphorus-sulfur co-doped non-noble metal zinc-air battery catalyst by respectively taking diphenyl disulfide as a sulfur source, a chlorine phosphate tripolymer as a phosphorus source and triethylamine as a stabilizer, so as to obtain the supported nitrogen-phosphorus-sulfur co-doped non-noble metal zinc-air battery catalyst. The preparation method comprises the following steps: loading a sulfur source and a phosphorus source on a ZIF-8 carrier, and finally annealing in a nitrogen atmosphere to obtain the loaded nitrogen-phosphorus-sulfur co-doped non-noble metal zinc-air battery catalyst. According to the invention, a high-coordination non-noble metal monatomic catalyst is co-modified by nitrogen, sulfur and phosphorus, so that high oxygen reduction performance and stability are realized under alkaline conditions, and the problem of high cost of a zinc-air battery catalyst caused by scarcity of a platinum-based metal catalyst is solved to a certain extent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of zinc-air batteries, and particularly relates to a preparation method of a supported nitrogen, phosphorus, and sulfur co-doped non-precious metal zinc-air battery catalyst. Background Art

[0002] Currently, efficient oxygen reduction still relies on platinum-based metal catalysts. Due to the scarcity of platinum resources globally and the poor stability of the catalyst itself, it has encountered many obstacles in large-scale popularization and application. Against this background, the research on developing high-performance and economically viable oxygen reduction electrocatalysts as alternatives has become crucial. Single-atom catalysts are regarded as ideal alternatives to platinum-based oxygen reduction catalysts due to their maximum atomic utilization efficiency and tunable electronic properties.

[0003] In recent years, single-atom catalysts have attracted extensive research interest due to their high catalytic activity, stability, selectivity, and nearly 100% atomic utilization efficiency. CN 117334928 A discloses a supported nitrogen and phosphorus co-doped iron single-atom bifunctional electrocatalyst. Using ZIF-8 as a precursor, after introducing an iron source, it is coated with a polymer and then pyrolyzed and phosphated to anchor Fe single atoms in N, P co-doped porous carbon. This catalyst is used in the oxygen reduction reaction and has a relatively high half-wave potential under alkaline conditions. However, the preparation of this catalyst requires a two-step pyrolysis process, which may lead to uneven dispersion of single atoms on the support and has a certain risk of atomic aggregation, which is not conducive to large-scale industrial production and application. In 2024, the research group of Wang Qiang (Energy & Environmental Science, 2024, 17, 249 - 259) synthesized ZIF-8 / FePc@PZS by adding iron phthalocyanine (FePc) to a typical zeolitic imidazolate framework (ZIF-8) and encapsulating FePc in the cavity of ZIF-8 without changing the crystal structure; then coating a uniform layer of phosphazene polymer (PZS) on its surface. Subsequently, Fe-N 4 SP / NPS-HC was prepared by one-step pyrolysis and acid etching of ZIF-8 / FePc@PZS. This catalyst has good oxygen reduction performance under alkaline conditions, but the preparation of this catalyst requires acid etching, which not only causes partial loss of the material and reduces the yield, but also produces some acidic wastewater, causing pollution to the environment. Summary of the Invention

[0004] Aiming at the problems existing in the prior art, the present invention provides a preparation method of a supported nitrogen, phosphorus and sulfur co-doped non-precious metal zinc-air battery catalyst with simple operation and good oxygen reduction performance. This method only requires one-step calcination. By co-modifying non-precious metal single atoms with nitrogen, sulfur and phosphorus, while improving the oxygen reduction performance and stability of the catalyst, the economic cost is greatly reduced, and the problems of too high cost and low stability of the zinc-air battery catalyst are solved.

[0005] The method for the non-precious metal zinc-air battery catalyst provided by the present invention includes the following steps:

[0006] Step 1: Disperse zinc nitrate and cetyltrimethylammonium bromide in deionized water to obtain solution A; disperse 2-methylimidazole in deionized water to obtain solution B; mix solution A and solution B, stir to make the two solutions mix evenly, then centrifuge and wash, and vacuum dry the obtained precipitate to obtain the ZIF-8 support.

[0007] Step 2: Disperse the ZIF-8 support obtained in Step 1 in methanol, then add a non-precious metal salt, stir to make it mix evenly, add diphenyl disulfide and phosphoryl chloride trimer, stir to mix evenly, add triethylamine, stir for 10 - 24 hours, then centrifuge and wash, vacuum dry the obtained precipitate, and finally anneal in a nitrogen atmosphere to obtain a supported nitrogen, phosphorus and sulfur co-doped non-precious metal zinc-air battery catalyst; based on the mass of the catalyst being 100%, the loading amount of the non-precious metal in the supported nitrogen, phosphorus and sulfur co-doped non-precious metal zinc-air battery catalyst is 0.5% - 1.2%.

[0008] Further, in the above Step 1, preferably, the mass ratio of zinc nitrate, 2-methylimidazole, and cetyltrimethylammonium bromide is 1:10 - 15:0.02 - 0.04.

[0009] Further, in the above Step 2, preferably, the non-precious metal salt is any one of bismuth nitrate, calcium nitrate, barium nitrate, cerium nitrate, iron nitrate, cobalt nitrate, chromium nitrate, copper nitrate, magnesium nitrate, and nickel nitrate.

[0010] Further, in the above Step 2, preferably, the mass ratio of the ZIF-8 support, diphenyl disulfide, phosphoryl chloride trimer, and triethylamine is 1:0.4 - 2:0.3 - 0.5:3 - 20.

[0011] Further, in the above Step 2, more preferably, the mass ratio of the ZIF-8 support, diphenyl disulfide, phosphoryl chloride trimer, and triethylamine is 1:0.7 - 1.5:0.3 - 0.5:6 - 10.

[0012] Further, in the above Steps 1 and 2, the temperature of the vacuum drying is 60 - 80°C and the time is 20 - 24 hours.

[0013] Further, in the above step 2, the annealing temperature is 900 - 1100 °C, and the time is 1 - 5 hours.

[0014] Further, in the above step 2, preferably, the heating rate of the annealing is 3 - 8 °C / minute.

[0015] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0016] The present invention first prepares a ZIF-8 support by reacting 2-methylimidazole with zinc nitrate. This support is beneficial for providing more active sites and improving stability. Then, a non-precious metal salt is mixed with this support, and then diphenyldisulfide and phosphoric acid chlorotrimer are used for polymerization coating. After pyrolysis, a non-precious metal zinc-air battery catalyst is obtained. This catalyst can increase the number of active sites and improve the catalytic activity through the co-modification of nitrogen, sulfur, and phosphorus on non-precious metal single atoms. Moreover, the present invention further improves the stability of the catalyst through a high-temperature annealing method. The present invention constructs a non-precious metal single-atom catalyst through the co-modification of nitrogen, sulfur, and phosphorus, greatly reducing the cost. At the same time, its oxygen reduction performance is still very high (half-wave potential 0.90 - 0.94 V), and it maintains high efficiency and stability (the half-wave potential remains basically unchanged after 30,000 cycles). To a certain extent, it solves the problems of high cost and low stability faced by current zinc-air battery catalysts, and has a great technological breakthrough. Description of the Drawings

[0017] Figure 1 is the XRD pattern of the supported nitrogen, sulfur, and phosphorus co-doped bismuth single-atom catalyst in Example 1.

[0018] Figure 2 is the aberration-corrected HAADF-STEM image of the supported nitrogen, sulfur, and phosphorus co-doped bismuth single-atom catalyst in Example 1.

[0019] Figure 3 is the LSV curve of the supported nitrogen, sulfur, and phosphorus co-doped bismuth single-atom catalyst prepared in Example 1 in a 0.1 mol / L aqueous potassium hydroxide solution.

[0020] Figure 4 is the stability test diagram of the supported nitrogen, sulfur, and phosphorus co-doped bismuth single-atom catalyst prepared in Example 1 before and after the reaction. Detailed Embodiments

[0021] The present invention will be described in detail below with reference to the drawings and specific embodiments, but the protection scope of the present invention is not limited to these embodiments only.

[0022] Example 1

[0023] Step 1: Dissolve 1.5 g of zinc nitrate and 50 mg of cetyltrimethylammonium bromide in 50 mL of deionized water to obtain solution A; Disperse 15 g of 2-methylimidazole in 300 mL of deionized water to obtain solution B; Quickly mix solution A and solution B, stir to make the two solutions mix evenly, then centrifuge. After the obtained precipitate is washed with deionized water, it is dried in vacuum at 80 °C for 20 hours, and the white powder is collected to obtain the ZIF-8 support.

[0024] Step 2: Disperse 200 mg of the ZIF-8 support in 20 mL of methanol, then add 0.6 g of bismuth nitrate, and stir to make it mix evenly to obtain solution C; Disperse 150 mg of diphenyldisulfide and 70 mg of phosphoric acid chlorotrimer in 200 mL of methanol, and stir to make it mix evenly to obtain solution D; Add solution D to solution C, stir to mix evenly, add 1.3 g of triethylamine thereto, stir for 20 hours, then centrifuge and wash. The obtained precipitate is dried in vacuum at 80 °C for 24 hours, and finally annealed at a heating rate of 5 °C / minute to 1100 °C in a nitrogen atmosphere for 2 hours. After natural cooling, the powder is collected to obtain a supported nitrogen, sulfur, and phosphorus co-doped bismuth single-atom catalyst (denoted as Bi SAs / PSNC-1000); Based on the mass of the catalyst being 100%, the loading amount of bismuth in this catalyst is 0.8%.

[0025] It can be seen from Figure 1 and Figure 2 that the nitrogen, sulfur, and phosphorus co-doped bismuth appears in the form of single atoms. Figure 3 This is the LSV curve of Bi SAs / PSNC-1000 measured in 0.1 mol / L potassium hydroxide aqueous solution. It can be seen that the half-wave potential is 0.93 V, which proves that this catalyst has high-performance oxygen reduction performance. Figure 4 This is the stability test of the catalyst. It can be seen that the half-wave potential of the catalyst remains basically unchanged after 30,000 cycles, which proves that this catalyst has high stability.

[0026] In step 2 of the above Example 1, the annealing temperature was adjusted to 900 °C, 1000 °C, and 1200 °C respectively for carrying out, and other steps were the same as those in Example 1. The obtained catalysts were respectively marked as Bi SAs / PSNC-900, Bi SAs / PSNC-1000, and Bi SAs / PSNC-1200. The half-wave potential tests were respectively carried out on the obtained catalysts, and the test results are shown in Table 1.

[0027] Table 1 Comparison of half-wave potentials of catalysts prepared at different annealing temperatures

[0028] Catalyst <![CDATA[E 1 / 2 (V)]]> Test solution Bi SAs / PSNC-900 0.907 0.1 mol / L aqueous potassium hydroxide solution Bi SAs / PSNC-1000 0.915 0.1 mol / L aqueous potassium hydroxide solution Bi SAs / PSNC-1100 0.930 0.1 mol / L aqueous potassium hydroxide solution Bi SAs / PSNC-1200 0.921 0.1 mol / L aqueous potassium hydroxide solution

[0029] As can be seen from Table 1, the half-wave potentials of the catalysts annealed at 900-1200 °C are all relatively high. Among them, the catalyst annealed at 1100 °C has a more positive half-wave potential, showing better oxygen reduction performance. This is because the active sites of the exposed metal on the support require a certain temperature, but too high a temperature will lead to the loss of metal active sites, thereby affecting the activity. Therefore, in step 2 of the following examples, the annealing temperature is 1100 °C.

[0030] Example 2

[0031] In step 2 of this example, 0.6 g of calcium nitrate was used to replace bismuth nitrate in Example 1, and the other steps were the same as in Example 1, to obtain a supported nitrogen, sulfur, and phosphorus co-doped calcium single-atom catalyst. Based on 100% of the mass of the catalyst, the calcium loading of this catalyst is 0.6%.

[0032] Example 3

[0033] In step 2 of this example, 0.6 g of barium nitrate was used to replace bismuth nitrate in Example 1, and the other steps were the same as in Example 1, to obtain a supported nitrogen, sulfur, and phosphorus co-doped barium single-atom catalyst. Based on 100% of the mass of the catalyst, the barium loading of this catalyst is 0.9%.

[0034] Example 4

[0035] In step 2 of this example, 0.6 g of cerium nitrate was used to replace bismuth nitrate in Example 1, and the other steps were the same as in Example 1, to obtain a supported nitrogen, sulfur, and phosphorus co-doped cerium single-atom catalyst. Based on 100% of the mass of the catalyst, the cerium loading of this catalyst is 1.2%.

[0036] Example 5

[0037] In step 2 of this example, 0.6 g of iron nitrate was used to replace bismuth nitrate in Example 1, and the other steps were the same as in Example 1, to obtain a supported nitrogen, sulfur, and phosphorus co-doped iron single-atom catalyst. Based on 100% of the mass of the catalyst, the iron loading of this catalyst is 0.5%.

[0038] Example 6

[0039] In step 2 of this example, 0.6 g of cobalt nitrate was used to replace bismuth nitrate in Example 1, and the other steps were the same as in Example 1, to obtain a supported nitrogen, sulfur, and phosphorus co-doped cobalt single-atom catalyst. Based on 100% of the mass of the catalyst, the cobalt loading of this catalyst is 0.7%.

[0040] Example 7

[0041] In step 2 of this example, 0.6 g of chromium nitrate was used to replace bismuth nitrate in Example 1, and the other steps were the same as those in Example 1, obtaining a supported nitrogen, sulfur, and phosphorus co-doped chromium single-atom catalyst. Based on 100% of the mass of the catalyst, the chromium loading in this catalyst was 0.8%.

[0042] Example 8

[0043] In step 2 of this example, 0.6 g of copper nitrate was used to replace bismuth nitrate in Example 1, and the other steps were the same as those in Example 1, obtaining a supported nitrogen, sulfur, and phosphorus co-doped copper single-atom catalyst. Based on 100% of the mass of the catalyst, the copper loading in this catalyst was 0.8%.

[0044] Example 9

[0045] In step 2 of this example, 0.6 g of magnesium nitrate was used to replace bismuth nitrate in Example 1, and the other steps were the same as those in Example 1, obtaining a supported nitrogen, sulfur, and phosphorus co-doped magnesium single-atom catalyst. Based on 100% of the mass of the catalyst, the magnesium loading in this catalyst was 1.1%.

[0046] Example 10

[0047] In step 2 of this example, 0.6 g of nickel nitrate was used to replace bismuth nitrate in Example 1, and the other steps were the same as those in Example 1, obtaining a supported nitrogen, sulfur, and phosphorus co-doped nickel single-atom catalyst. Based on 100% of the mass of the catalyst, the nickel loading in this catalyst was 1%.

[0048] Example 11

[0049] In step 2 of this example, the amount of diphenyldisulfide was increased to 350 mg, and the other steps were the same as those in Example 1, obtaining a supported nitrogen, sulfur, and phosphorus co-doped bismuth single-atom catalyst. Based on 100% of the mass of the catalyst, the bismuth loading in this catalyst was 0.7%.

[0050] Example 12

[0051] In step 2 of this example, the amount of triethylamine was reduced to 0.7 g, and the other steps were the same as those in Example 1, obtaining a supported nitrogen, sulfur, and phosphorus co-doped bismuth single-atom catalyst. Based on 100% of the mass of the catalyst, the bismuth loading in this catalyst was 0.8%.

[0052] Example 13

[0053] In step 2 of this example, the amount of triethylamine was increased to 3.6 g, and the other steps were the same as those in Example 1, obtaining a supported nitrogen, sulfur, and phosphorus co-doped bismuth single-atom catalyst. Based on 100% of the mass of the catalyst, the bismuth loading in this catalyst was 0.7%.

[0054] Example 14

[0055] In step 2 of this example, the dosage of triethylamine was increased to 2.2 g, and other steps were the same as those in Example 1, obtaining a supported nitrogen-sulfur-phosphorus co-doped bismuth single-atom catalyst. Calculated based on the mass of the catalyst being 100%, the loading amount of bismuth in this catalyst was 0.8%.

[0056] The half-wave potential tests were respectively carried out on the catalysts obtained in the above Examples 2 to 14, and the test results are shown in Table 2.

[0057] Table 2 Comparison of half-wave potentials of the catalysts prepared in Examples 2 to 14

[0058] Catalyst <![CDATA[E 1 / 2 (V)]]> Test solution Example 2 0.91 0.1 mol / L aqueous potassium hydroxide solution Example 3 0.91 0.1 mol / L aqueous potassium hydroxide solution Example 4 0.90 0.1 mol / L aqueous potassium hydroxide solution Example 5 0.92 0.1 mol / L aqueous potassium hydroxide solution Example 6 0.91 0.1 mol / L aqueous potassium hydroxide solution Example 7 0.90 0.1 mol / L aqueous potassium hydroxide solution Example 8 0.90 0.1 mol / L aqueous potassium hydroxide solution Example 9 0.91 0.1 mol / L aqueous potassium hydroxide solution Example 10 0.90 0.1 mol / L aqueous potassium hydroxide solution Example 11 0.91 0.1 mol / L aqueous potassium hydroxide solution Example 12 0.92 0.1 mol / L aqueous potassium hydroxide solution Example 13 0.91 0.1 mol / L aqueous potassium hydroxide solution Example 14 0.91 0.1 mol / L aqueous potassium hydroxide solution

Claims

1. A method for preparing a supported nitrogen, phosphorus and sulfur co-doped non-precious metal zinc-air battery catalyst, characterized in that: The following steps are involved: Step 1: Dispersing zinc nitrate and hexadecyltrimethylammonium bromide in deionized water to obtain solution A; 2-Methylimidazole is dispersed in deionized water to obtain solution B; solution A is mixed with solution B, and the two solutions are stirred to be evenly mixed, and then centrifuged and washed, and the obtained precipitate is vacuum dried to obtain a ZIF-8 carrier; Step 2: Disperse the ZIF-8 carrier obtained in step 1 in methanol, then add a non-precious metal salt, stir to mix evenly, add diphenyl disulfide and chlorophosphate trimer, stir to mix evenly, add triethylamine, stir for 10 to 24 hours, centrifuge, wash, vacuum dry the obtained precipitate, and finally anneal in a nitrogen atmosphere to obtain a supported nitrogen-phosphorus-sulfur co-doped non-precious metal zinc-air battery catalyst; Based on 100% of the mass of the catalyst, the loading amount of the non-noble metal in the supported nitrogen, phosphorus and sulfur co-doped non-noble metal zinc-air battery catalyst is 0.5% to 1.2%.

2. The method for preparing the supported nitrogen, phosphorus and sulfur co-doped non-noble metal zinc-air battery catalyst according to claim 1, characterized in that: In step 1, the mass ratio of the zinc nitrate, 2-methylimidazole and hexadecyltrimethylammonium bromide is 1:10-15:0.02-0.

04.

3. The method for preparing the supported nitrogen, phosphorus and sulfur co-doped non-noble metal zinc-air battery catalyst according to claim 1, characterized in that: In step 2, the non-precious metal salt is any one of bismuth nitrate, calcium nitrate, barium nitrate, cerium nitrate, iron nitrate, cobalt nitrate, chromium nitrate, copper nitrate, magnesium nitrate, and nickel nitrate.

4. The method for preparing a supported nitrogen, phosphorus and sulfur co-doped non-noble metal zinc-air battery catalyst according to claim 1, characterized in that: In step 2, the mass ratio of the ZIF-8 carrier, diphenyl disulfide, chlorophosphate trimer, and triethylamine is 1:0.4-2:0.3-0.5:3-20.

5. The method for preparing a supported nitrogen, phosphorus and sulfur co-doped non-noble metal zinc-air battery catalyst according to claim 1, characterized in that: In step 2, the mass ratio of the ZIF-8 carrier, diphenyl disulfide, chlorophosphate trimer, and triethylamine is 1:0.7-1.5:0.3-0.5:6-10.

6. The method for preparing a supported nitrogen, phosphorus and sulfur co-doped non-noble metal zinc-air battery catalyst according to claim 1, characterized in that: In step 1 and step 2, the vacuum drying temperature is 60 to 80° C. and the time is 20 to 24 hours.

7. The method for preparing a supported nitrogen, phosphorus and sulfur co-doped non-noble metal zinc-air battery catalyst according to claim 1, characterized in that: In step 2, the annealing temperature is 900-1100° C. and the time is 1-5 hours.

8. The method for preparing a supported nitrogen, phosphorus and sulfur co-doped non-noble metal zinc-air battery catalyst according to claim 1 or 7, characterized in that: In step 2, the heating rate of the annealing is 3-8°C / min.

Citation Information

Patent Citations

  • Supported nitrogen-phosphorus co-doped iron monatomic difunctional electrocatalyst and application thereof

    CN117334928A

  • Multi-heteroatom codoped hollow porous carbon material, preparation method and application thereof

    CN108383098A

  • N and P co-doped carbon-supported transition metal monatomic material, preparation method and application thereof

    CN114517306A

  • Iron atom cluster / phosphorus-nitrogen-sulfur doped carbon material as well as preparation method and application thereof

    CN115632135A

  • Electroreduction of co2 in acidic conditions using a catalyst having a dual co generation and c-c coupling function

    WO2024160799A1